2021
DOI: 10.3390/ijms222312734
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 Induces Early Epithelial Mesenchymal Transition in Human Proximal Tubular Epithelial Cells through Activation of IL-6/STAT3 Pathway

Abstract: Particulate matter exposure has been known as a potential risk for the global burden of disease, such as respiratory and cardiovascular diseases. Accumulating evidence suggests that PM2.5 (particulate matter with a diameter less than 2.5 μm) is associated with increased risk of kidney disease, but the mechanisms underlying the renal injury caused by PM2.5 remain to be elucidated. This study investigated the effects of PM2.5 on human proximal tubular epithelial (HK-2) cells by monolayer and 3D spheroid cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This further illustrates the pivotal role of IL-6 in the etiology of CsA-induced AKI. Epithelial-mesenchymal transition (EMT) is observed in not only renal fibrosis, 31,32 but also occurs in the acute phase of kidney injury. 33 In this study, the increased expression of EMT-related genes, Ptk2 , Mmp9 , Jun , and Myd88 , were also observed in mice with CsA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further illustrates the pivotal role of IL-6 in the etiology of CsA-induced AKI. Epithelial-mesenchymal transition (EMT) is observed in not only renal fibrosis, 31,32 but also occurs in the acute phase of kidney injury. 33 In this study, the increased expression of EMT-related genes, Ptk2 , Mmp9 , Jun , and Myd88 , were also observed in mice with CsA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, EMT marker, vimentin and α-SMA, was increased in mice with CsA-induced AKI (Supplementary Figure 3), which had been seen before by some researchers. 32 Thus, inhibition of EMT-related genes will be effective in mice at risk for progressive kidney injury. Interestingly, the role of Kras , Itga6 , and Cd4 in AKI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous addition of IL-6 to ovarian cancer cells activated STAT3 and mesenchymal cell marker expression and enhanced cell motility [32]. Furthermore, neutralizing IL-6 signaling was sufficient to reverse the EMT characteristics of human proximal tubular epithelial cells induced by PM2.5 [33]. In peritoneal fibrosis, IL-6 also stimulates EMT [34].…”
Section: Il-6-induced Cellular Processes Associated With Fibrosismentioning
confidence: 98%
“…The link between PTX3 and tubulo-interstitial damage, always based upon HK-2 PTCs, has been also investigated in order to evaluate the effects of particulate matter with a diameter less than 2.5 μm (PM 2.5). In vitro studies using HK-2 cells distributed as a monolayer and 3D spheroid cultures showed not only progressive EMT in the observed cell line but was also associated with increased IL-6 production and the activation of signal transducer and activator of transcription 3 (STAT3) which is involved in EMT [28]. The same group, in the same in vitro setting with HK-2 cells, determined also, after PM 2.5 exposure, increased PTX3 mRNA expression levels; moreover, in the absence of PTX3, such as in the previous model of IR injury, IL-6 level were higher and the EMT process more pronounced [29].…”
Section: Ptx3 and Ckd Progressionmentioning
confidence: 99%